Sufis and salafis in the contemporary age - Ridgeon, Lloyd V. J. (Bloomsbury Academic, 2015)
"Sufis and Salafis in the Contemporary Age explores the dynamics at play between what are usually understood as two very different forms of Islam, namely Sufism and Salafism. Sufism is commonly understood as the peaceful and mystical dimension of Islam whereas Salafism is perceived as strictly pietistic and moralist, and for some it conjures up images of violent manifestations of Islam.Of course these generalisations require more nuanced investigation, and this book provides a number of case studies from around the Islamic world to unpack the intricate relationship between the two. The diversity of the case studies that focus on Islamic groups in India, Iraq, Egypt, Morocco, Turkey and South East Europe reflect the multiplicity of relationships that exist between the Salafis and Sufis. The specific case studies are framed by an introduction that provides essential historical background and definitions of the terms, and also by general studies of the Sufi-Salafi relationship which enable the reader to focus on the large picture. This will be the first book to investigate the relationship between Sufism and Salafism in such a wide fashion, and includes chapters on "traditional" Sufis, as well as from those who consider that Sufism and Salafism are not necessarily contradictory."--